2002
DOI: 10.1007/s11664-002-0109-4
|View full text |Cite
|
Sign up to set email alerts
|

Studies of electroless nickel under bump metallurgy—Solder interfacial reactions and their effects on flip chip solder joint reliability

Abstract: The electroless-deposited Ni-P under bump metallurgy (UBM) layer was fabricated on Al pads for Sn containing solder bumps. The amount of P in the electroless Ni film was optimized by controlling complexing agents and the pH of plating solution. The interfacial reaction at the electroless Ni UBM/solder interface was investigated in this study. The intermetallic compound (IMC) formed at the interface during solder reflowing was mainly Ni 3 Sn 4 , and a Prich Ni layer was also formed as a by-product of Ni-Sn reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 7 publications
3
35
0
Order By: Relevance
“…Especially, the reactions between Ni(P)|Au-coated soldering pads and solders have been studied extensively. [8][9][10][11][12][13][14][15][16][17] Likewise, the cracking of interconnections soldered on the Ni(P) metallization has also been reported in these papers and the occurrence of the failure is typically explained by the oxidation or contamination of the plating bath that affects the quality of the metallization.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the reactions between Ni(P)|Au-coated soldering pads and solders have been studied extensively. [8][9][10][11][12][13][14][15][16][17] Likewise, the cracking of interconnections soldered on the Ni(P) metallization has also been reported in these papers and the occurrence of the failure is typically explained by the oxidation or contamination of the plating bath that affects the quality of the metallization.…”
Section: Introductionmentioning
confidence: 99%
“…5,9 To observe the nano-voids formed in the Ni-Sn-P layers of the 0 and 3 MTO samples, the interfaces of the 0 and 3 MTO samples were observed by cross-sectional TEM; the results are shown in Fig. 10.…”
Section: Resultsmentioning
confidence: 99%
“…The formation mechanisms of Kirkendall voids have been discussed in detail in our previous work [3]. Jeon et al [27] used shear testing with a SnPb solder ball on Ni-P UBM and found Kirkendall voids on the fracture surface after reflow at 250C for 16 minutes. So, they attributed the decrease of solder joint strength to the existence of Kirkendall voids.…”
Section: Effect Of Thermal Aging On Solder Joint Fracture Behaviormentioning
confidence: 96%